Eight in One: Hidden Diversity of the Bagrid Catfish Tachysurus albomarginatus s.l. (Rendhal, 1928) Widespread in Lowlands of South China - Shao, Wei-Han; Cheng, Jian-Li; Zhang, E (Frontiers in Genetics, 2021)
There is increasing evidence that species diversity is underestimated in the current taxonomy of widespread freshwater fishes. The bagrid species T.albomarginatus s.l. is mainly distributed in the lowlands of South China as currently identified. A total of forty localities (including the type locality), which covers most of its known range, were sampled. Molecular phylogenetic analyses based on concatenated mtDNA and nuclear genes recover nine highly-supported lineages clustering into eight geographic populations. The integration of molecular evidence, morphological data and geographic distribution demonstrates the delineation of T. albomarginatus s.l. as eight putative species. Four species, namely T. albomarginatus, T. lani, T. analis and T. zhangfei sp. nov. and the T. similis complex are taxonomically recognized herein. Moreover, T. zhangfei sp. nov. comprises two genetically distinct lineages with no morphological and geographical difference. This study also reveals aspects of estimation of divergence time, distribution and ecological adaption within the T. albomarginatus group. The unraveling of the hidden species diversity of this lowland bagrid fish highlights the need for not only the molecular scrutiny of widely distributed species of South China, but also for the adjustment of current biodiversity conservation strategies to protect the largely overlooked diversity of fishes from low elevation rapids.